Kebenaran Prosedural versus Kebenaran Substantif: Dialektika Kuasa dalam Kethoprak Lakon “Saridin Andum Waris” - Ramadhan, Yusuf; Purnomo, Sucipto Hadi; Nugroho, Yusro Edy (Lingua Susastra, 2023)
This study examines the construction of truth in the Kethoprak play "Saridin Andum Waris" performed by Bhakti Kuncoro Pati in 2022. Using a sociology of literature approach, we analyze how the play's storyline reflects substantive truth, exploring its relationship to procedural truth. Our data, comprising characters, plot, and settings, is examined in relation to the lived experiences of these elements in Javanese society. The analysis reveals that "Saridin Andum Waris" prioritizes substantive truth over procedural truth. This manifests in the play's conflicts, which arise and unfold due to irrationalities and emotional motivations rather than through legal or logical sequences. This suggests the play engages with deeper societal truths beyond surface-level legal or factual accuracy. By exploring the play's construction of truth, this study offers new insights into Kethoprak's role in reflecting and critiquing Javanese society. It also highlights the potential of dramatic works to delve into nuanced and subjective understandings of truth beyond established legal or rational frameworks.